The Influence of Influencer Credibility on Wardah's Impulsive Buying Intention Through the Mediation of Brand Attitude and Product Attractiveness - Syifa Rahadatul Aisyi; Muh. Abdul Aziz; Leonita Siwiyanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid development of digital marketing has encouraged cosmetic companies to utilize influencer marketing strategies to influence consumer perceptions and purchasing behavior. This study aims to analyze the influence of influencer credibility on impulsive purchase intention through the mediating roles of brand attitude and product attractiveness among Wardah consumers in Sukabumi. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 161 respondents who had purchased Wardah products through TikTok Shop in Sukabumi. The sampling technique used was purposive sampling, while data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results indicate that influencer credibility, represented by influencer attractiveness and influencer trustworthiness, has a positive and significant effect on brand attitude and product attractiveness. Furthermore, brand attitude and product attractiveness have a positive and significant influence on impulsive purchase intention. The mediation analysis shows that brand attitude and product attractiveness play important roles in explaining the relationship between influencer credibility and impulsive purchase intention. These findings indicate that credible influencers can strengthen consumers’ positive perceptions toward brands and products, which ultimately encourages spontaneous purchasing behavior. This study contributes to digital marketing literature by explaining the mechanism through which influencer credibility affects impulsive buying behavior in the cosmetic industry. The findings provide practical implications for cosmetic companies in selecting credible influencers and developing effective digital marketing strategies.